All the hearts you eat - Piper, Hailey (Titan Books, 2024)
"What really happened to Cabrina Brite? Ivory's life changes irrevocably when she discovers the body of Cabrina Brite on the sands of Cape Morning, along with a mysterious poem. How did she die, and why does it seem she was trying to swim to Ghost Cat Island, the center of so many local mysteries? Desperate to uncover the answers surrounding Cabrina's death, and haunted by her discovery, Ivory begins to see the pale ghost of Cabrina, only to shake it off as a mere hallucination. But Ivory is not alone. Cabrina's closest friends have also seen a similar apparition, and as they toy with occult possibilites, they begin to unravel the truth behind Cabrina's death. Because Cape Morning isn't a ghost town, but a town filled with ghosts, and Ivory is about to discover just what happens when you let one in."--from page 4 of cover.